2012
DOI: 10.1039/c2sc20800h
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate as a redox co-catalyst for the aerobic Pd-catalyzed oxidation of unactivated sp3-C–H bonds

Abstract: This paper describes a new method for the catalytic aerobic oxygenation of unactivated sp3-C–H bonds. This transformation utilizes Pd(OAc)2 as a catalyst in conjunction with NaNO3 as a redox co-catalyst. Both oxime ether and pyridine derivatives are effective directing groups for these reactions. The oxygen incorporated into the product derives from the solvent (acetic acid). Preliminary results show that the addition of simple NaCl to the reaction mixture results in aerobic chlorination under analogous condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
87
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(107 citation statements)
references
References 47 publications
(22 reference statements)
6
87
0
10
Order By: Relevance
“…For example, Bao recently used sodium nitrite as a cocatalyst to achieve aerobic trifluoroacetoxylation of methane [18] and Sanford used sodium nitrate as an additive in ligand-directed aerobic acetoxylation of sp 3 C-H bonds [19]. Older precedents exist for application of similar concepts in the oxidation of benzene.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bao recently used sodium nitrite as a cocatalyst to achieve aerobic trifluoroacetoxylation of methane [18] and Sanford used sodium nitrate as an additive in ligand-directed aerobic acetoxylation of sp 3 C-H bonds [19]. Older precedents exist for application of similar concepts in the oxidation of benzene.…”
Section: Introductionmentioning
confidence: 99%
“…8 Sanford and co-workers reported that nitrate/nitrite could serve as a redox co-catalyst in the aerobic ace-toxylation of unactivated C(sp 3 )–H bonds via C–O bond reductive elimination of a high-valent palladacycle (Scheme 2A). 9 Very recently, the Grubbs group reported a palladium-catalyzed aerobic alkene diacetoxylation method mediated by a catalytic amount of silver nitrite (Scheme 2B). 10 We reasoned that a palladium-catalyzed aerobic aminooxygenation reaction might be possible using this electron transfer mediator strategy, as an NO x species could be a kinetically suitable mediator in the aerobic oxidation of the alkylpalladium(II) intermediate formed after aminopalladation.…”
mentioning
confidence: 99%
“…13 The other necessary solvent component, Ac 2 O, could possibly sequester H 2 O generated in the catalytic system. 9 …”
mentioning
confidence: 99%
“…Several directing groups such as 2-pyridyl, carbonyl, ester, nitrile, carboxylic acid, N-acetyl and amide can be efficiently used for the reaction. With the assistance of these directing groups, acetoxylation (Henry, 1971;Yoneyama and Crabtree, 1996;Sanford et al, 2004;Yu et al, 2005;Yu et al, 2006;Corey et al, 2006;Wu et al, 2008;Chen et al, 2009;Cheng et al, 2010;Yu et al, 2010;Yu et al, 2011;Sanford et al, 2012;Kim et al, 2013), alkoxylation (Sanford et al, 2006;Wang and Yuan, 2010), hydroxylation (Yu et al, 2009;Dong et al, 2012) and benzoxylation (Sanford et al, 2005;Cheng et al, 2011) at the ortho C-H bond of directing group substituted aromatics with various oxygen nucleophiles have been studied. Palladium and copper complexes are efficient catalysts for this type of reaction.…”
Section: Introductionmentioning
confidence: 99%